Assessment of knowledge, attitude, practices and effect of patient education among diabetic patients - SRILATHA KONDISETTY; HARIKA JANAGAMA; SURAJ PASUNOORI; RAJANI GUNNAM (International Journal of Pharma and Bio Sciences, 2018)
Diabetic complications has been increasing rapidly in developing countries especially in India. This may be probably due to lack of knowledge and awareness of diabetes and its associated complications. The aim of the study is to assess knowledge, attitude, practices and effect of patient education in reducing the risk of diabetic complications. A prospective study was conducted among 80 diabetic patients at Outpatient Department of General Medicine. First line screening tests( Random Blood Sugar, Blood Pressure, Electrocardiogram, Serum Creatinine, lipid profile, fundus examinations) and KAP was taken before counselling. The study population were been counselled regarding disease, life style modifications, medication use for a period of time. After providing education, screening tests and KAP was again conducted. Out of 80 patients 43( 53.75% ) were males and 37( 46.25% ) were females. There was a statistical significant improvement in the mean KAP scores before ( 26.40±6.322 ) and after ( 58.82±2.848 ) counselling ( P<0.0001*** ) and also in the laboratory values (P<0.033). A better understanding of disease not only controls but also helps in minimizing risk of complications.